Disarmament leaflet, 1987 (1987)
1987 1960-2000 "Disarmament leaflet, 1987" [T0555.jpg], 1987 This leaflet, entitled 'Your health isn't the only thing nuclear weapons damage', was published by the Trade Union Campaign for Nuclear Disarmament in 1987.